174k views
4 votes
9x-4y9 /-3x-3y-2 Need help.

User Jlmt
by
6.6k points

1 Answer

3 votes
y9) ((9•(x-4))•—————————————)•y(-2) -(3)(-3)x(-3)
Simplify —-(3)(-3)x(-3)
((9 • (x-4)) • -27x3y9) • y(-2) (32x(-4) • -27x3y9) • y(-2) x(-4) multiplied by x3 = x((-4) + 3) = x(-1) = 1/x1 = 1/x 32 multiplied by 33 = 3(2 + 3) = 35 -35x(-1)y9 • y(-2) y9 multiplied by y(-2) = y(9 + (-2)) = y7
Final result : -35x(-1)y7 I believe this is the answer :) ( pls tell me if I am wrong and have a great day!)
User Demian Brecht
by
5.8k points